РОЗРАХУНОК ЕЛЕКТРОМЕХАНІЧНИХ СИЛ У ЗШИТІЙ ПОЛІЕТИЛЕНОВІЙ ІЗОЛЯЦІЇ КАБЕЛІВ БІЛЯ ВОДНИХ МІКРОДЕФЕКТІВ ПРИ ЇХ ПОШИРЕННІ - Щерба, М.А. (Інститут електродинаміки Національної академії наук України, 2018)
Electromechanical forces arising at the poles of water micro-inclusions and at the tips of trees in cross-linked polyethylene insulation of ultra-high-voltage cables in an alternating electric field are studied. The finite element method was used to carry out the numerical experiments on the calculation of electrical field and mechanical stresses in the insulation arising under the action of dielectrophoresis forces as the result of influence of electric field on the water microdefects. The features of the change in these stresses are determined depending on the nature of the distribution of the defects in the insulation material: the configuration of inclusions, the number of the branches of the trees and directions of its germination. The most dangerous configurations of defects that cause the greatest local stresses are determined. These stresses can exceed tens of MPa and they are comparable to the ultimate mechanical stress limit for cross-linked polyethylene and therefore they can lead to local destruction of the material. Mechanical fatigue of the material in a strong electric field in the presence of moisture can be a reason of the irreversible aging of the insulation of ultrahigh-voltage cables, which is observed during their long-term operation. References 11, figures 7.